Convertir el caos en cosmos: la lógica del laberinto en apocalipsis cum figuris de Luisa Josefina Hernández - González Treviño , Ana Elena (Amaltea. Revista de Mitocrítica, 2009)
In this article I trace the way in which Luisa Josefina Hernández’s medieval fiction, Apocalipsis cum figuris, contains recurring labyrinth motifs, especially surrounding the concept of circumambulation and the cyclical repetition of atavistic conduct. Characters are only capable of transcending atavism by surrendering to the logic of the labyrinth. By subverting both novelistic and mythical conventions, and through the narrator’s quasi-scientific detachment, the author establishes a contemporary tone without thereby sacrificing the redeeming design of the novel.